Clerodendranthus spicatus: a comprehensive review of the chemical constituents, pharmacology, quality control and clinical applications - Jiao, Xingmeng; Jin, Qiong; Zhu, Peifeng; Tan, Zhuomin; Li, Li; Liu, Lu (Frontiers in Pharmacology, 2025)
Clerodendranthus spicatus (CS), is an herbaceous perennial belonging to the family Lamiaceae. The herb is extensively employed in traditional Chinese medicine for the mitigation of nephritis, cystitis, kidney stones, urological tract stones, gout, and other urinary conditions. Numerous research studies have been conducted in the past to explore the traditional medicinal value, phytochemical composition, pharmacological effects, and quality control measures associated with this plant. This has motivated us to systematically search various online databases such as Google Scholar, PubMed, Science Direct, Elsevier, CNKI, Scopus, Embase, and Web of Science using specific keywords to get the most recent research information findings related to this plant. Phytochemical investigations have identified that this plant predominantly contains flavonoids, terpenoids, phenylpropanoids, and volatile oil compounds. Certain constituents have been employed as markers in quality assessment research, and some were recognized as bioactive agents in the management of specific ailments. These components have demonstrated notable effectiveness in combating bacterial infections, reducing inflammation, providing antioxidant properties, managing hyperuricemia, and offering renal protection. Notably, clinical trials have confirmed its remarkable efficacy in treating urinary inflammation and stones. We acquired recent research findings concerning CS in the fields of phytochemistry, pharmacology, quality control, and clinical applications via online search. These findings have been summarized and analysed to offer a valuable reference for further comprehensive research, development, and utilization of CS.